A Critical Analysis of Minutes of Companies Proceeding in Nigeria: Problems and Recommendations - Okonkwo, Ifeanyi Emmanuel (International Journal For Research In Business, Management And Accounting, 2015)
Over the years, we have seen and heard of corrupt Directors forging the minutes and resolutions ofa company in other to fraudulently obtain loans from banks. We have heard and seen forceful takeovers without proper resolutions only for us to find such lies enshrined in a ghost-minutes of thecompany. We have seen present members rendered absent in the minutes even though we can swearwe saw them present. Yes! virtually all that a company does is recorded and in the event of adispute, enquiry, query, investigation, meetings, resolutions, et al, one important document orrecord which substantially stand as evidence in resolving or denying any transaction is the minutesof the proceedings of the company. Indeed any foreign holding or subsidiary or partnershipcompany as well as investors may want to know about the legal effects of the Minutes. The minutesbecome in the letters of the Companies & Allied Matters Act, a prima facie evidence of companiesproceedings. The effect is that whatever is so recorded in the minutes, so far the chairman’ssignature is affixed, is the truth of the proceedings. Although, the Act allowed for a rebuttal of theminutes with other proofs, but the Act did not state any other way in which the content of theminutes may be disproved. Again the form in which minutes are to be kept in line with the present1990 Act is another setback. Indeed, prior to the enactment of CAMA and with recent judicialauthorities, the judicial view was that Minute entries made in loose sheets of paper, whether kept ina file or fastened together in a bound book subsequently, were not admissible/permitted evidence ofthe Minutes of the deliberations and decisions taken at such a meeting (See Onwuka v. Taymani &Ors [1965] NCLR page 203; and the English case - Heart of Oaks Ass. v. James Lower & SonsLtd[1936] Ch.D page 26) Later the Supreme Court in Chika Brothers Case held differently ininterpreting the 1968 Act which unfortunately does not tally literarily with the present 1990 Act.Infact, the situation becomes more disturbing going by the general rule of evidence that no extrinsicevidence of certain documentary evidence is allowed. We can indeed only hope to come under itsexceptions, but again, practically speaking, its exceptions are difficult to prove within the settings ofa company. This leads to grave dangers in that anyone in the company, especially its Directors, mayforge a resolution or otherwise against the company provided the chairman’s signature can beforged or generated (moreso, if it is the chairman). The same goes for the board meetings andothers. The very principle of corporate governance and its checks and balances is surely incompletewithout a proper legal framework to safeguard that most indispensable and invaluable book of acompany – The minutes.